Multi-omic profiling of peritoneal metastases in gastric cancer identifies molecular subtypes and therapeutic vulnerabilities - Tanaka, Yosuke; Chiwaki, Fumiko; Kojima, Shinya; Kawazu, Masahito; Komatsu, Masayuki; Ueno, Toshihide; Inoue, Satoshi; Sekine, Shigeki; Matsusaki, Keisuke; Matsushita, Hiromichi; Boku, Narikazu; Kanai, Yae; et al. (Nature cancer, 2021)
Peritoneal metastasis, a hallmark of incurable advanced gastric cancer (GC), presently has no curative therapy and its molecular features have not been examined extensively. Here we present a comprehensive multi-omic analysis of malignant ascitic fluid samples and their corresponding tumor cell lines from 98 patients, including whole-genome sequencing, RNA sequencing, DNA methylation and enhancer landscape. We identify a higher frequency of receptor tyrosine kinase and mitogen-activated protein kinase pathway alterations compared to primary GC; moreover, approximately half of the gene alterations are potentially treatable with targeted therapy. Our analyses also stratify ascites-disseminated GC into two distinct molecular subtypes: one displaying active super enhancers (SEs) at the ELF3, KLF5 and EHF loci, and a second subtype bearing transforming growth factor-β (TGF-β) pathway activation through SMAD3 SE activation and high expression of transcriptional enhancer factor TEF-1 (TEAD1). In the TGF-β subtype, inhibition of the TEAD pathway circumvents therapy resistance, suggesting a potential molecular-guided therapeutic strategy for this subtype of intractable GC.